Proving Hegel Wrong: Learning the right lessons from European integration for the African Continental Free Trade Area - Andrew Mold (Journal of African Trade, 2021)
This paper sets out to disprove the German philosopher Hegel's dictum about people learning nothing from history, by looking at the lessons to be learned for the African Continental Free Trade Area (AfCFTA) from the European Union's experience of regional integration. Since its foundation in 1957, European integration has had a chequered history, with its fair share of triumphs and setbacks. This paper focuses on the evidence from economic studies and the lessons to be gleaned from the Single Market Programme (SMP), which was initiated in 1993 and ushered in the creation of a unified European market. The parallels are far from perfect: structurally, in the level of development and resources available to support regional integration, there are major differences between the SMP and the AfCFTA. Nevertheless, this paper highlights nine major lessons for the African continent from the SMP, including the scale of benefits to be expected, the role of multinational corporations, the need for an effective competition policy and the importance of public buy-in to the process.
Keywords: 330; AfCFTA; European Union; single market programme; deep integration